Jasmonic acid enhances osmotic stress responses by MYC2‐mediated inhibition of protein phosphatase 2C1 and response regulators 26 transcription factor in tomato. (29th December 2022) - Zhao, Wenchao; Huang, Huang; Wang, Jingjing; Wang, Xiaoyun; Xu, Bingqin; Yao, Xuehui; Sun, Lulu; Yang, Rui; Wang, Jianli; Sun, Aidong; Wang, Shaohui
SUMMARY: The jasmonic acid (JA) signaling pathway is involved in the plant response to drought stress. JA and other hormones synergistically regulate the drought response in plants. However, the molecular mechanism underlying this synergism remains poorly defined. In the present study, transcriptome analyses of guard cells and quantitative PCR experiments revealed that MYC2 negatively regulated the negative regulator of ABA signaling, SlPP2C1, and the type‐B response regulator in the cytokinin pathway, SlRR26, and this negative regulation was direct. SlRR26 overexpression reduced drought tolerance in transgenic tomatoes, whereas slrr26 cr lines were more tolerant to drought. SlRR26 negatively modulated reactive oxygen species levels in stomata and stomatal closure through RobhB . Moreover, SlRR26 overexpression counteracted JA‐mediated stomatal closure, suggesting that SlRR26 played a negative role in the JA‐mediated drought response. These findings suggest that MYC2 plays a key role in JA‐regulated stomatal closure under drought stress by inhibiting SlPP2C1 and SlRR26 . Significance Statement: Little is known about the mechanisms by which jasmonic acid regulates stomatal movement in response to drought stress. The present study helps our understanding of the potential mechanism of jasmonic acid‐modulated stomatal dynamics in response to drought stress and demonstrates that MYC2 plays an essential role in this process by interacting with key members of the ABA and cytokinin signaling pathways.